2017
DOI: 10.1167/iovs.17-21450
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognition Analysis of Age-Related Retinal Ganglion Cell Signatures in the Human Eye

Abstract: PurposeTo characterize macular ganglion cell layer (GCL) changes with age and provide a framework to assess changes in ocular disease. This study used data clustering to analyze macular GCL patterns from optical coherence tomography (OCT) in a large cohort of subjects without ocular disease.MethodsSingle eyes of 201 patients evaluated at the Centre for Eye Health (Sydney, Australia) were retrospectively enrolled (age range, 20–85); 8 × 8 grid locations obtained from Spectralis OCT macular scans were analyzed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(115 citation statements)
references
References 70 publications
(155 reference statements)
6
109
0
Order By: Relevance
“…1C), each frame was manually assessed and corrected for segmentation error if pronounced layer misclassification, resulting in more than 50% difference in thickness to adjacent areas, was detected by an experienced operator (NY) following previously established protocol. 21 A total of 21.6% of the grids required manual correction and 4.6% individual grids were excluded from analysis as adequate segmentation was hindered due to the presence of major blood vessels; shadowing; poor quality B-scan (<15 dB signal scores); the optic nerve head encroached the grid; or more than 10% of the grid could not be analyzed because it was located outside of the scan area. Subanalysis confirmed that manual adjustments did not bias final measurements (Supplementary Fig.…”
Section: Ganglion Cell Count Estimatementioning
confidence: 99%
See 4 more Smart Citations
“…1C), each frame was manually assessed and corrected for segmentation error if pronounced layer misclassification, resulting in more than 50% difference in thickness to adjacent areas, was detected by an experienced operator (NY) following previously established protocol. 21 A total of 21.6% of the grids required manual correction and 4.6% individual grids were excluded from analysis as adequate segmentation was hindered due to the presence of major blood vessels; shadowing; poor quality B-scan (<15 dB signal scores); the optic nerve head encroached the grid; or more than 10% of the grid could not be analyzed because it was located outside of the scan area. Subanalysis confirmed that manual adjustments did not bias final measurements (Supplementary Fig.…”
Section: Ganglion Cell Count Estimatementioning
confidence: 99%
“…21,[44][45][46] The age difference between individual subjects and the cohorts may therefore increase the variability within the dataset and confound the comparison of structure-function relationship between the normal and glaucomatous cohort. Hence, to minimize the variability imposed by intra-and intercohort age differences, the GCL thickness and DLS of all normal and glaucomatous subjects were age-corrected to the average age of the glaucomatous cohort using previously established regression analysis models as conducted in previous studies, 11,21,[24][25][26]31,32,45,47 including the commonly used SITAstandard algorithm of the HFA. 48 Specifically, for the GCL thickness, measurements from each normal and glaucomatous subjects were clustered into eight statistically separable classes and adjusted to match the average age of the glaucomatous cohort using a previously published conversion for all but the foveal area.…”
Section: Age Correctionmentioning
confidence: 99%
See 3 more Smart Citations